2020
DOI: 10.1002/sd.2136
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the green growth indicators to achieve sustainable development: A novel extended interval‐valued intuitionistic fuzzy‐combined compromise solution approach

Abstract: Recent years have witnessed the green growth as a renowned efficient approach to tracking the progress towards sustainable development. The paper is mainly aimed to propose an innovative extended approach based on Combined Compromise Solution (CoCoSo) and Interval‐Valued Intuitionistic Fuzzy Set (IVIFS); thus, it is called IVIF Combined Compromise Solution (IVIF‐CoCoSo). This study is the first effort that used the fuzzy sets theory and decision‐making technique (entitled IVIF‐CoCoSo) to rank and evaluate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 67 publications
1
22
0
Order By: Relevance
“…Efforts to replace plastic bags with paper bags have negative impacts on land use because more trees are needed [32]. Ongoing discussions of how to measure green growth [33,34] cast doubts on existing indexes and decoupling projections and coalesce with controversy on what should be considered a green job [35] or green exports (Kang and Lee in this SI) (4). As a logical consequence of the precautionary principle of sustainability [36], if we cannot trust that we adequately measure the potential negative impacts of activities related to green growth, such activities should not be carried out.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts to replace plastic bags with paper bags have negative impacts on land use because more trees are needed [32]. Ongoing discussions of how to measure green growth [33,34] cast doubts on existing indexes and decoupling projections and coalesce with controversy on what should be considered a green job [35] or green exports (Kang and Lee in this SI) (4). As a logical consequence of the precautionary principle of sustainability [36], if we cannot trust that we adequately measure the potential negative impacts of activities related to green growth, such activities should not be carried out.…”
Section: Discussionmentioning
confidence: 99%
“…It must be pointed out that the combined compromise solution (CoCoSo) method was firstly presented by Yazdani [18], which employs a comparability sequence through two means named aggregated exponentially weighted product (EWP) and simple additive weighting (SAW). Up to now, the CoCoSo method has been triumphantly used in personnel assessment [19], tourism attraction selection [20], and green growth indicator [21]. However, we will face diverse practical problems with complex data during decision-making process.…”
Section: A Discussion On the Evolution Of Cocoso Approachmentioning
confidence: 99%
“…Liao et al [52] introduced an innovative Pythagorean fuzzy CoCoSo method for the selection of cold chain logistics delivery center. Alrasheedi et al [53] suggested a novel IVIF-CoCoSo technique for assessing the green growth indicators to accomplish sustainable development in the manufacturing region. Rani and Mishra [54] gave a single-valued neutrosophic CoCoSo method for evaluating sustainable waste electrical and electronics equipment recycling partners.…”
Section: Combined Compromise Solution (Cocoso) Methodsmentioning
confidence: 99%